Effects of Mercury Exposure, Community Behavior, and Activities on Contact Dermatitis in a Watershed Area, 2024 - Rahmi, Sintha Defiza; Djafri, Defriman; Ramadani, Mery (Jurnal Kesmas Jambi, 2025)
Contact dermatitis is a skin disease with the highest prevalence compared to other types of skin disorders.This study examines the influence of mercury (Hg) exposure levels, community behavior, and activity patterns on the incidence of contact dermatitis in the Batang Tebo River flow, Bungo District, in 2024. The study employed a matched case-control design. The minimum sample size was 49 pairs, with an additional 10% added to account for potential non-response, resulting in a target of 54 matched pairs. After data collection, the final sample consisted of 51 matched pairs with a case-to-control ratio of 1:1. Samples were selected using simple random sampling with matching based on sex. Primary data were collected through interviews with respondents. Case data were obtained from the medical records at Air Gemuruh Primary Health Center. Bivariate analysis identified variables significantly associated with contact dermatitis: mercury (Hg) exposure level (OR = 5.8; 95% CI: 2.24–14.98), bathing activity (OR = 8.5; 95% CI: 3.01–23.95), and contact frequency (OR = 5; 95% CI: 1.91–13.06). Multivariate modeling showed that bathing activity was the most dominant factor influencing the incidence of contact dermatitis.